Electron-ion collider transverse instabilities due to the crab cavity fundamental impedance - T. Mastoridis; T. Loe; M. Blaskiewicz (Physical Review Accelerators and Beams)
The electron-ion collider crab Cavities will present a significant transverse impedance to the beam. The low-level radio frequency system will have to reduce the crab cavity impedance to prevent transverse instabilities, while regulating the crabbing voltage and minimizing the radio frequency noise levels injected into the beam. This work presents an estimate of the crab cavity impedance in the presence of feedback and the resulting stability margins using simplified stability criteria. Generalized stability criteria are also presented in this work and are used to more accurately estimate stability margins.